Seroprevalence of Anti-S1-RBD Antibodies in Pre-pandemic and Pandemic Subjects From Hail Region, KSA - Sherwani, Subuhi; Khan, Mohd Wajid Ali; Mallik, Arshi; Khan, Mahvish; Saleem, Mohd; Raafat, Mohamed; Shati, Ayed A.; Alam, Noor (Frontiers in Public Health, 2022)
Background: Two years into the pandemic, the threat of new SARS-CoV-2 variants still looms large. Sustained efforts are required to fully understand the infection in asymptomatic and individuals with complications. Identification, containment, and preventative strategies rely on understanding the varied humoral immune responses. Methods: An in-house ELISA was developed and standardized to screen for serum IgG antibodies against SARS-CoV-2 S1-RBD protein as antigen. The current study aims to investigate the seroprevalence of serum antibodies against S1-RBD antigen in pre-pandemic and during the early pandemic period in subjects from Hail region, KSA and correlate with clinical and demographic factors. Results: Samples collected from both male and female subjects during the pandemic in the age groups of 20-40 (0.31 ± 0.029 and 0.29 ± 0.024, respectively) and 41-60 years (0.35 ± 0.026 and 0.30 ± 0.025, respectively), showed significantly higher levels of serum antibodies against S-RBD antigen as compared to the age-matched pre-pandemic samples. Pandemic subjects exhibited significantly (p < 0.01) higher inhibition (80-88%) compared to age-matched pre-pandemic subjects (32-39%). Neutralizing antibodies against S1-RBD antigen were detected in about 10% of the total pre-pandemic (males and female). However, subjects >60 years did not show neutralizing antibodies. Conclusion: Neutralizing antibody levels were found to increase in samples collected during the pandemic, even though these subjects were not clinically Covid-19 positive cases. A small number of pre-pandemic subjects showed cross-reactive serum neutralizing antibodies, suggesting prior exposure to other coronaviruses in the region. With, waning neutralizing antibodies levels and reduced vaccine efficacy against newer variants, the need to develop better assays for surveillance, management and future research development continues to be essential.